O romance português : 1974-2024 - Miguel Real (Cahiers d’histoire.)
The novel in Portugal between 1974 and 2020 is divided into two phases: 1. 1974 and 2000: the Late Modernist or Neomodernist Novel, which socially and politically corresponds to Portugal's integration into Europe; 2. 2000-2020: the Post-Modern Novel, following the literary rhythm of Europe, corresponding to the phase of Late Capitalism. The main objective of Portuguese literature in the first phase is to modernize the country, to participate in European literature, to be as European as France. Being a modern country meant in 1974: 1. Expressing oneself in total freedom, the end to censorship, of any kind; 2. Overcoming the economic poverty in which the population survived; 3. Overcoming the illiteracy and ignorance which plagued the majority of the population; 4. Ending a 13-year colonial war and allowing the colonies to become independent; 5. Democratizing state institutions; 6. Finally, changing the country's course, replacing the historic privilege attributed to the Atlantic with the privilege attributed to Europe. In the second phase, a new generation emerges in Portuguese literature with novels published from 2000 onwards: Gonçalo M. Tavares is its main actor.